Simultaneous spectral recovery of long-period grating sensor array using optical time-division multiplexing - Lin H.S.; Mokhtar M.R.; Rahman F.A.; Rashid H.A.A.; Roslina M.; Arif N.A.M. (2023)
A novel sensor network based on optical time-division multiplexing (OTDM) is proposed and demonstrated for simultaneous sensing of long-period grating (LPG) sensor array with overlapping spectra. A star network is configured by pairing a circulator with each of the LPG sensors. Experiments are conducted by measuring the changes of surrounding refractive index at different sensors, which show excellent agreement between the demultiplexed and pristine transmission spectrum of the LPG sensors. 2011 Published by Elsevier GmbH.